2010
DOI: 10.1002/art.27690
|View full text |Cite
|
Sign up to set email alerts
|

The proteasome inhibitor bortezomib drastically affects inflammation and bone disease in adjuvant‐induced arthritis in rats

Abstract: Objective. To explore the effect of bortezomib in splenocytes and fibroblast-like synoviocytes (FLS) and its in vivo potency in a rat model of adjuvant-induced arthritis (AIA), which resembles human rheumatoid arthritis (RA).Methods. AIA was induced with Freund's complete adjuvant. Splenocyte and FLS proliferation and apoptosis were measured by radioactivity incorporation and flow cytometry, respectively. The invasiveness of FLS from rats with AIA was tested in a Transwell system. The pattern of cytokine secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 50 publications
(51 reference statements)
3
46
0
1
Order By: Relevance
“…In keeping with the blocking effects of MG262 on the cell cycle, MG262 inhibited the proliferation (DNA replication) of nasal fibroblasts. These results concur with the marked inhibition of cell proliferation after the incubation of fibroblast-like synoviocytes with bortezomib, at the same concentration (10 nM) used in our study (Yannaki et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In keeping with the blocking effects of MG262 on the cell cycle, MG262 inhibited the proliferation (DNA replication) of nasal fibroblasts. These results concur with the marked inhibition of cell proliferation after the incubation of fibroblast-like synoviocytes with bortezomib, at the same concentration (10 nM) used in our study (Yannaki et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The kinetics and sensitivity (IC 50 ) of MG262 and bortezomib inhibition was similar to those reported for bortezomib in cancer cell lines (Hideshima et al, 2001;Codony-Servat et al, 2006). Our results concur with those reported in human pulmonary fibroblasts using the proteasome inhibitor benzyloxycarbonylleucyl-leucyl-leucine aldehyde (MG132) (You and Park, 2011) and bortezomibtreated rat fibroblast-like synoviocytes (Yannaki et al, 2010), but contrast with those of Fineschi et al (2006Fineschi et al ( , 2008. The latter, using a similar experimental approach and analytical method, found that MG262 and proteasome inhibitor I decreased the viability of human dermal fibroblasts only when used at very high (micromolar) concentrations after 72 h of culture (Fineschi et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Bzb, a modified dipeptidyl boronic acid that reversibly inhibits the chymotrypsinlike activity of the 26S proteasome, is the first proteasome inhibitor approved by the FDA for clinical use to treat multiple myeloma [15]. In addition to its anti-tumor effects, Bzb has also been shown to affect inflammation of mimicked rheumatoid arthritis in animal models [16,17], but little is known about the effects of Bzb on the expression of inflammation after TJR. Wear debris generated around implanted prostheses is well accepted as the major initiating event in the development of inflammatory osteolysis and subsequent aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…51 When used in animal RA models there was a marked reduction in disease severity, inflammatory cytokines and fibroblast like synoviocytes became more pro-apoptopic as well as less invasive. 52,53 Furthermore T-cells from RA patients when treated exvivo with bortezomib were increasingly anergic, pro-apoptopic, and had a reduced inflammatory cytokine profile. 54 Furthermore in SLE animal models bortezomib slows disease onset and ameliorates disease phenotype.…”
Section: Nuclear Factor Kappa-light Chain Enhancer Of Activated B Celmentioning
confidence: 99%